Factors Associated with Vancomycin Nephrotoxicity in the Critically Ill. Issue 5 (September 2015) - Hanrahan, T. P.; Kotapati, C.; Roberts, M. J.; Rowland, J.; Lipman, J.; Roberts, J. A.; Udy, A.
Vancomycin is a glycopeptide antibiotic commonly used in the management of methicillin-resistant Staphylococcus aureus infection. The recent increase in prevalence of methicillin-resistant Staphylococcus aureus with reduced susceptibility to vancomycin has prompted experts to advocate for higher target trough serum concentrations. This study aimed to evaluate the potential consequences of more aggressive vancomycin therapy, by examining the association between higher serum concentrations and acute kidney injury (AKI) in a population of critically ill patients. We collected data for all patients who received vancomycin over a five-year period and evaluated the prevalence of new-onset AKI using the Risk, Injury, Failure, Loss and End-stage (RIFLE) kidney disease criteria. One-hundred and fifty-nine patients provided complete data, with 8.8% manifesting new onset AKI while receiving vancomycin. The median age was 57 (44 to 68) years, while the median trough serum concentration was 16 (10 to 19) mg/l. Multivariate logistic regression analysis identified mean trough concentration (OR=1.174, P =0.024), APACHE II score (OR=1.141, P =0.012) and simultaneous aminoglycoside prescription (OR=18.896, P =0.002) as significant predictors of AKI. These data suggest higher trough vancomycin serum concentrations are associated with greater odds of AKI in the critically ill.